2018 IEEE Wireless Communications and Networking Conference (WCNC) 2018
DOI: 10.1109/wcnc.2018.8377225
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of high-speed trains using 5G new radio synchronization signals

Abstract: We study positioning of high-speed trains in 5G new radio (NR) networks by utilizing specific NR synchronization signals. The studies are based on simulations with 3GPP-specified radio channel models including path loss, shadowing and fast fading effects. The considered positioning approach exploits measurement of Time-Of-Arrival (TOA) and Angle-Of-Departure (AOD), which are estimated from beamformed NR synchronization signals. Based on the given measurements and the assumed train movement model, the train pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…How to exploit these new characteristics is a largely open problem. As this paper is being written, very few or no publications can be found concerning NR and indoor localization, whereas some initial studies are available for outdoor communications [272].…”
Section: B Heterogeneous Networking Protocolsmentioning
confidence: 99%
“…How to exploit these new characteristics is a largely open problem. As this paper is being written, very few or no publications can be found concerning NR and indoor localization, whereas some initial studies are available for outdoor communications [272].…”
Section: B Heterogeneous Networking Protocolsmentioning
confidence: 99%
“…High-speed train positioning using 5G only is simulated in [43], where a track of over 43 km is modeled, with variable train velocity of up to 400 km/h. Using channel models suitable for the considered scenario, and AoD and ToA measurements with the EKF-based tracking model, the authors declare a mean positioning accuracy of 0.66 m (below the 1 m 5G target), with 95% errors below 1.7 m, and 99% ones below 2.3 m. Separate PSS/SSS sequence identities are assigned to RRHs uniformly located at 500 m intervals along the upper side of the railroad, at a distance of 15 m from the railroad.…”
Section: Results Analysismentioning
confidence: 99%
“…Despite the promising outcomes, it is observed that, whenever the train acceleration changes, the tracking algorithm introduces a lag, which affects the tracking accuracy over a certain period. In the works by both Maymo-Camps et al [38] and Talvitie et al [43], the attained performances are expressed in terms of mean positioning accuracy; however, details about the statistical distribution of the measurements are not provided, and the coverage factor used to compute the accuracy is not specified as well. Additionally, despite being based on the fusion of different technologies, i.e., GNSS and 5G, the former study does not analyze the uncertainty propagation associated to the combination of different quantities to derive the position information.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations